ANALISIS KERUSAKAN HOSE SISTEM HIDROLIK PADA EXCAPATOR TIPE EC55B PRO (Studi Kasus Di Dinas Bina Marga Kabupaten Kuningan) - Riki Irfan; fery firmansyah (Jurnal Fakultas Teknik Kuningan, 2022)
Excavator is one of the heavy equipment used to move materials. The hydraulic system is a component that functions as work equipment on units that utilize the work of the hydraulic system. Damage that often occurs in excavators is in the excavator system. This type of research uses qualitative methods by conducting direct observations in the field. This analysis aims to analyze the damage, the causative factors, how to repair and prevent damage to the hydraulic system of the EC55B Pro heavy equipment excavator and to determine the force loss on the hydraulic cylinder caused by damage to the hydraulic system. The inspection procedure is carried out by performing a performance test consisting of an operating speed test and a pressure test. Visual inspection is also carried out on the hose, charging pump, control valve, hydraulic cylinder, main pump, servo mechanism and travel motor. The results of the analysis found damage to the housing, charging pump, lever swash plate, hydraulic cylinder seal kit, hose and travel motor shaft caused by contamination of hydraulic oil with water and errors in unit operation. Repair steps are carried out by replacing components that are damaged as a whole (assy). Preventive actions are carried out by carrying out daily checks and preventive maintenance according to procedures.